The Value of a Two-Sided Real Swaption (Journal of Mathematical Study, 2022)
In this paper we establish a mathematical model for two-sided matching swaption problems in real world. We find a necessary matching condition of the two-sided swaption and deduce analytical formulations of the swaptions in virtue of pricing kernel methods. Also we explore the optimal exercise boundary and properties of the swaptions for investment decision making.